THE CONCEPT AND APPLICATION OF THE MINIMALIST LIFESTYLE ON QURAN PERSPECTIVE - Novia Hamidah Yulianti (Universitas Ahmad Dahlan, 2021)
Lifestyle is a natural thing, not triggered by certain things such as advertisements, living environment, and so on. As is known, meeting the needs is already important, but if it exceeds the limit, it means that it cannot be said to be normal or reasonable. Lifestyle is a pattern of action that distinguishes one person or group from another. If the lifestyle is as an ideology, it will form an identity that is individual or group and distinguishes it from others. Lifestyle has a goal to then be able to form an image that is proud of both users and participants. The image displayed through a lifestyle is more often in contact with a person's various appearances and has properties that can be captured and felt by the senses. The image that arises on the lifestyle chosen by a person is closely related to values ​​and social status. The concept of a minimalist lifestyle is in harmony with Islamic values. In the Qur'an itself the concept of minimalist living has been explained in several suras. The concept of minimalist living is also exemplified by the Prophet and his family. The concept of a lifestyle that teaches behavior not to overdo it in life, whether it's about eating, shopping, or dressing. The concept of minimalist living also teaches you to prioritize what is more needed in life, using what is around you as efficiently as possible. Reducing the number of items or collections owned is included in the concept of minimalist living. Appreciating and caring for what you currently have is also part of the minimalist living concept. In Surah Al-A'raf verse 31, it is explained that you must wear clothes and choose food or drinks within reasonable limits, not excessive. Then in Surah Al-Isra 'verse 26 it is explained that there is a prohibition on wasting the property owned. Then in the same sura, verse 27, it is explained that waste is a reflection of the devil's brothers.